2006
DOI: 10.1080/00087114.2006.10797924
|View full text |Cite
|
Sign up to set email alerts
|

Basic and molecular cytogenetics in freshwater Cichlidae (Osteichthyes, Perciformes). Karyotypic conservationism and divergence

Abstract: -The chromosomes of one Cichlasoma /acetum and three Geophagus brasiliensis populations from the headwaters of adjacent river basins (Parana State, southern Brazil), were investigated using differential staining techniques (C-banding, Ag-NORs, DAPI and CMA 3 ) and fluorescent in situ hybridization (FISH) with 18S rDNA and 5S rDNA probes. The diploid chromosome number (2n) was invariably 48 in the four populations, with karyotypes composed of 3 submetacentric and 21 subtelo/acrocentric chromosome pairs in G. br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
32
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 22 publications
13
32
0
2
Order By: Relevance
“…In the Cichlidae family, karyotypic analysis have demonstrated the maintenance of the diploid number in most species. As observed to the most of Neotropical cichlids, the diploid number of 48 chromosomes was constant in both G. basiliensis here analyzed, corroborating with the ancestral condition for both Cichlidae and Perciformes (THOMPSON 1979;FELDBERG;BERTOLLO, 1985;MARTINS et al, 1995;VICARI et al, 2006;RONCATI et al, 2007;PERAZZO et al, 2010). However, this diploid number can vary between 32 and 60 chromosomes (FELDBERG et al, 2003) in some cichlids species.…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…In the Cichlidae family, karyotypic analysis have demonstrated the maintenance of the diploid number in most species. As observed to the most of Neotropical cichlids, the diploid number of 48 chromosomes was constant in both G. basiliensis here analyzed, corroborating with the ancestral condition for both Cichlidae and Perciformes (THOMPSON 1979;FELDBERG;BERTOLLO, 1985;MARTINS et al, 1995;VICARI et al, 2006;RONCATI et al, 2007;PERAZZO et al, 2010). However, this diploid number can vary between 32 and 60 chromosomes (FELDBERG et al, 2003) in some cichlids species.…”
Section: Discussionsupporting
confidence: 62%
“…This ditribuition pattern was observed to Feijão and Pântano streams populations. Vicari et al (2006) showed a peculiar pattern of distribution of heterochromatin in G. brasiliensis river Jaguaiaíva presenting some pairs conspicuous heterochromatic blocks and instersticiais. So, in G. brasiliensis populations minors chromosomal divergences could be atribuited to heterochromatin expansion or exchange how observed in both populations analized.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations